Analisis kesulitan belajar peserta didik kelas IVB SDN 1 Gabusan pada materi FPB & KPK di masa pandemi Covid-19 berdasarkan kecerdasan logis matematis - Najmul Laila; Riyadi Riyadi; Muhammad Ismail Sriyanto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
Abstract. This research aims to describe the types and causes of learning difficulties for class IVB students at SDN 1 Gabusan on FPB and KPK materials during the Covid-19 pandemic based on logical mathematical intelligence. This research uses a qualitative descriptive research method with a case study approach. Determination of the subject in the research using purposive sampling technique. This research uses test data collection techniques and task-based interviews. The data validity technique used in this research is time triangulation. Data analysis techniques include identifying all data, reducing data, compiling data in units, validating data to making conclusions. Based on the results of the research, it can be concluded that the type of learning difficulty of students with high logical mathematical intelligence is difficulty in using correct mathematical procedures. The types of learning difficulties of students with moderate mathematical logical intelligence are difficulties in determining the right solution strategy and difficulties in using correct mathematical procedures. The types of learning difficulties of students with low logical mathematical intelligence are difficulties in understanding the given problem, difficulty in determining the right solution strategy, and difficulty in using correct mathematical procedures. The causes of learning difficulties for students with high logical mathematical intelligence are the limited learning time during the limited face-to-face implementation during the Covid-19 pandemic and the way teachers teach using the lecture learning method. The causes of learning difficulties for students with moderate mathematical logical intelligence are the limited learning time during the limited face-to-face implementation during the Covid-19 pandemic, the way teachers teach using the lecture learning method, and low interest in learning. The causes of learning difficulties in students with low logical mathematical intelligence are the limited learning time during the limited face-to-face implementation during the Covid-19 pandemic, the way teachers teach using the lecture learning method, low interest in learning, and an unsupportive family environment for learning. The level of logical mathematical intelligence of students is also one of the factors that affect learning difficulties.Keywords: learning difficulties, FPB & KPK, and mathematical logical intelligence